Severe Neurological Manifestation in a Child with Multisystem Inflammatory Syndrome - Mônica de Oliveira Santos; Diuly Caroline Ribeiro; Jordanna Sousa Rocha; Sibely Braga Santos Maia; André Luís Elias Moreira; Paulo Alex Neves Silva; Célia Regina Malveste Ito; Lilian Carla Carneiro; Melissa Ameloti Gomes Avelino (MDPI AG, 2022)
Background and objectives: During the COVID-19 pandemic, we followed with concern the evolution of several children diagnosed with Multisystem Inflammatory Syndrome in Children (MIS-C). The purpose of this study is to describe the evolution of MIS-C in a previously healthy 3-year-old girl. Methods: We tracked the daily medical report of all children admitted with suspected MIS-C to the five largest regional hospitals. Results: Our screening identified a child who had several neurological complications associated with MIS-C. We report hematological alterations, transient cardiac dysfunction, and cerebral involvements such as laminar cortical necrosis caused by ischemic stroke. We present the course of treatment and clinical outcome, and other complications such as a severe subglottic stenosis occurring after extubation. Conclusion: Subglottic stenosis is an expected complication after prolonged intubation, and the presence of dysphonia and/or stridor is an important predictive factor. MIS-C with severe neurological alteration may occur in a healthy child, and early diagnosis and treatment with a pulse of corticoid with immunoglobulin are essential for a favorable outcome.